Living Out Loud
1 online resource (464 pages)
Keywords: Living Out Loud: An Introduction to LGBTQ History, Society, and Culture offers students an evidence-based foundation in the interdisciplinary field of LGBTQ Studies. Chapters on history, diversity, dating/relationships, education, sexual health, and globalization reflect current research and thinking in the social sciences, humanities, and sciences. Coverage of current events and recommendations for additional readings, videos, and web resources help students apply the contents in their lives, making Living Out Loud the perfect core text for LGBTQ+ Studies (and similar) courses.